2011
DOI: 10.1371/journal.pone.0020989
|View full text |Cite
|
Sign up to set email alerts
|

Action and Emotion Recognition from Point Light Displays: An Investigation of Gender Differences

Abstract: Folk psychology advocates the existence of gender differences in socio-cognitive functions such as ‘reading’ the mental states of others or discerning subtle differences in body-language. A female advantage has been demonstrated for emotion recognition from facial expressions, but virtually nothing is known about gender differences in recognizing bodily stimuli or body language. The aim of the present study was to investigate potential gender differences in a series of tasks, involving the recognition of disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(149 citation statements)
references
References 66 publications
9
136
4
Order By: Relevance
“…Some studies have observed differences between male and female participants on this test (Alaerts, Nackaerts, Meyns, Swinnen, & Wenderoth, 2011;Carroll & Chiew, 2006;Dehning et al, 2012;Hallerbäck et al, 2009;Vellante et al, 2012;Voracek & Dressler, 2006;Yildirim et al, 2011), suggesting that women perform better at the RMET than men. Testing people who are inherently very good at this test and who might easily overcome subtle difficulties added by the translation might thus bias the validation.…”
Section: Limitationsmentioning
confidence: 84%
“…Some studies have observed differences between male and female participants on this test (Alaerts, Nackaerts, Meyns, Swinnen, & Wenderoth, 2011;Carroll & Chiew, 2006;Dehning et al, 2012;Hallerbäck et al, 2009;Vellante et al, 2012;Voracek & Dressler, 2006;Yildirim et al, 2011), suggesting that women perform better at the RMET than men. Testing people who are inherently very good at this test and who might easily overcome subtle difficulties added by the translation might thus bias the validation.…”
Section: Limitationsmentioning
confidence: 84%
“…To the best of our knowledge, only one paper thus far has presented a positive correlation between the RMET and ad hoc emotion recognition task (Alaerts, Nackaerts, Meyns, Swinnen, & Wenderoth, 2011). Emotional intelligence scale-faces is developed to measure the ability to recognize mimic expressions, a component of cognitive skill involved in emotional intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…One option for dealing with this complex problem is using more minimalistic and controlled stimuli depicting biological motion. Indeed, previous studies have shown that human observers can successfully recognize expressed emotions even in extremely impoverished stimuli such as point-light displays (Alaerts et al, 2011;Atkinson et al, 2004;Clarke et al, 2005;Dittrich et al, 1996;Nackaerts et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%